Autofiction in English (Palgrave Studies in Life Writing, 2018)
This innovative volume establishes autofiction as a new and dynamic area of theoretical research in English. Since the term was coined by Serge Doubrovsky, autofiction has become established as a recognizable genre within the French literary pantheon. Yet unlike other areas of French theory, English-language discussion of autofiction has been relatively limited - until now. Starting out by exploring the characteristic features and definitions of autofiction from a conceptual standpoint, the collection identifies a number of cultural, historical and theoretical contexts in which the emergence of autofiction in English can be understood. In the process, it identifies what is new and distinctive about Anglophone forms of autofiction when compared to its French equivalents. These include a preoccupation with the conditions of authorship; writing after trauma; and a heightened degree of authorial self-reflexivity beyond that typically associated with postmodernism. By concluding that there is such a field as autofiction in English, it provides for the first time detailed analysis of the major works in that field and a concise historical overview of its emergence. It thus opens up new avenues in life writing and authorship research.